1997
DOI: 10.1007/s001670050042
|View full text |Cite
|
Sign up to set email alerts
|

The anterior cruciate ligament does play a role in controlling axial rotation in the knee

Abstract: This study deals with the influence of peroperative ligament tension on total tibial rotation at different knee flexion angles. Fourteen human cadaver knees with a mean age of 56 years (range 42-84 years) were examined. The cadaver knees were subjected to internal/external (i/e) rotational torque of 6 Nm, at 10, 30, 50, 70 and 90 deg of knee flexion. The mean total i/e rotation with the anterior cruciate ligament (ACL) intact at 10 deg of knee flexion was 30.4 deg and after removing the ACL, 33.1 deg. At 10 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 19 publications
2
53
1
3
Order By: Relevance
“…Cadaveric studies revealed that the section of the ACL led to 2.4 to 4°increase in rotation in knee flexion angles below 30° [ 69,70]. Above this degree of flexion, the increase in rotation induced by the lesion was not detectable anymore [25,71]. Early in vivo studies demonstrated a similar increase of rotation in the injured knee by 10 % (3°) compared to the healthy knee [72].…”
Section: Knee Laxity In the Injured Knee Diagnosis Of Acl Injuriesmentioning
confidence: 98%
“…Cadaveric studies revealed that the section of the ACL led to 2.4 to 4°increase in rotation in knee flexion angles below 30° [ 69,70]. Above this degree of flexion, the increase in rotation induced by the lesion was not detectable anymore [25,71]. Early in vivo studies demonstrated a similar increase of rotation in the injured knee by 10 % (3°) compared to the healthy knee [72].…”
Section: Knee Laxity In the Injured Knee Diagnosis Of Acl Injuriesmentioning
confidence: 98%
“…3 The ACL primarily functions to limit anterior translation of the tibia relative to the femur, [4][5][6] and also plays a role in governing the coupled tibiofemoral axial rotation with knee flexion. 7,8 In vitro cadaveric studies have provided some insight into the behavior of the ACLdeficient knee under controlled conditions, 9,10 including simulated muscle loads, but here the relationship to the in vivo situation is not straightforward. In order to investigate the potential for ACL injury to elicit changes in knee kinematics during activity, precise dynamic studies of smallscale differences in motions are therefore important.…”
Section: Introductionmentioning
confidence: 99%
“…3 The effect on tibial rotation of cutting the ACL has been well reported. 4,5,6,7 In a cadaveric study, 4 total (internal and external) rotation at 10 and 30 degrees of knee " exion increased signi! cantly after the ACL was cut.…”
mentioning
confidence: 96%
“…12 Functional tests, which are designed to simulate the stress the knee encounters during selected functional activities, are both useful and simple to perform and are commonly used to determine such functional limitations as running and hopping in patients with ACL injuries. 5,13,14 Although unable to detect speci! c knee abnormalities, functional tests can be used to assess knee function in various clinical settings.…”
mentioning
confidence: 99%